Tinjauan yuridis konsekuensi pidana pada pelanggaran informed consent sebagai dasar transaksi terapeutik penyelenggaraan praktek kedokteran - Sherliana Hana Purwanti; Suryawan Raharjo; J S Murdomo (Kajian Hasil Penelitian Hukum, 2019)
The medical treatment, however low or high risk treatment is, it must always contain risks. An agreement on medical treatment will arise after the patient is given an adequate explanation of the disease, consequences, and side effects or risks that can occur from a medical treatment during the treatment process or the healing process of the disease. This study discusses juridical review of criminal consequences on violations of informed consent as the basis for therapeutic transactions in the implementaion of medical practice and how to prevent infringement of informed consent resulting in criminal consequences. Informed consent plays an important role in therapeutic transactions that lead to a medical treatment, that is as a form of patient approval after adequate information is given for medical treatment. This thesis study uses a normative juridical research method with a sociological juridical approach, namely research conducted by examining library materials or secondary data and also supported by field research to examine how the law works in the community. The research location is at Rumah Sakit Gigi dan Mulut Fakultas Kedokteran Gigi Universitas Jember and Sekretariat Persatuan Dokter Gigi Indonesia Cabang Kota Yogyakarta. Legal patient approval through informed consent can not be ignored by doctor at his own discretion. Although a certain medical treatment is needed, but the opinion of the doctor can not replace the patient’s consent. Doctors as health workers who have the authority to carry out informed consent are expected to realize the importance of the existence of informed consent and violations that result in criminal consequences. Patient should also be aware of the existence of informed consent as an inherent autonomous right.